Political and Energy Relations of Turkey and Russia (International relations and international law Journal, 2016)
Energy factor is a very important tool for strengthening the position and impact of Turkey not only on regional issues but also on the international geopolitics scale. The most significant condition for boosting economy, industry and foreign policy of Turkey is to secure new energy sources and routes for Ankara`s energy strategies. A nearly half of the energy resources are being imported by Turkey from Russia is consisted of natural gas. Trying to avoid to become totally depended on Russia`s energy deliveries, especially those of natural gas, Turkey is to be urged to implement new and alternative energy, transporting and logistic projects. These energy projects comprise such energy projects like TANAP, BТЕ, Nabucco, TAP, Trans-Caspian pipeline. In future, Turkey plans to decrease its dependence on Russia`s energy and fuel producers. There are extra energy exporting countries for Turkey that includes Azerbaijan, Turkmenistan, Kazakhstan, Iran and Iraq. As for Russia, it is interested in Turkey`s role as a big net importer and consumer of Russian energy resources. Turkey is also interested in maintaining good and smooth relations with Russia, which is seen by Ankara as a strategic strong and reliable partner. Russia needs and will need Turkish goods and products which are of good quality and not so high values. Turkey has definite interests in the importing of energy resources from Russia which is considered as a reliable and stabilizing factor.
Keywords: Turkey; Russia; energy; economy; strategy; project; partner; energy resources; natural gas; petroleum; pipelines; import; raw materials